Diffraction of sound waves on a metal ring - Карачун, Володимир Володимирович; Мельник, Вікторія Миколаївна; Фесенко, Сергій Вікторович (Technology audit and production reserves, 2016)
As the object of research, sensor unit as a multiphase mechanical construction in the operating conditions of hypersonic aircraft flight is exposed to actions of powerful external disturbances such as: ultra-high temperature – more than 2000 ºC, vibration, shock N-wave, acoustic penetrating radiation. Less harmful disturbances cause additional measurement errors of characteristics of the flight product. Clarification of the nature and origin in time and space of these errors is one of the most important tasks of navigation. Precisely delineated investigated phenomenon enables combat the negative influence of external disturbing factors by passive, active or autocompensation methods depending on character of the sensor error – methodological or instrumental. The obtained result confirms the presence of powerful and fluid motive flow with a spatial structure in a liquid-phase components of component base, which, in combination with generated sound waves form a zone of concentration of sound energy and, in accordance, development of three-dimensional turbulent fluid, and explains the emergence of areas of passive energy, in which is virtually absent turbulence. The expected effect of an efficient fight against the negative impact of penetrating sound radiation is based on eliminating an effect of aberrations and forming a powerful energy zones (zones of caustic surfaces), technical implementation of which in each case may have its advantages and disadvantages.